Summer knight a novel of the Dresden files - Butcher, Jim (New York : Roc, 2009)
Private detective/wizard-for-hire Harry Dresden is suckered into tangling in the affairs of Faerie, where the fate of the entire world-and his soul-are at stake.
Keywords: Dresden, Harry (Fictitious character); Wizards; Chicago (Ill.); Fantasy fiction